Overview of the pharmaceutical market of anticoagulants for the treatment of coronavirus disease (COVID-19) during marital state in Ukraine - O. M. Zaliska; O. M. Semenov (The State Expert Center of the Ministry of Health of Ukraine, 2022)
The war in Ukraine has not changed the epidemic situation with coronavirus disease (COVID-19). Further, new cases of disease and death among the population are recorded every day. A large number of people in shelters and bomb shelters, in transport during the evacuation, increases the risk of infection. One of the main complications that occur in patients with COVID-19 is the formation of blood clots, which can lead to negative consequences and death of the patient, and therefore, at the present stage, the use of anticoagulants in the form of low molecular weight heparins plays a very important role in the hospital treatment of coronavirus disease. Heparin potentially has advantages over other anticoagulants for its not only anticoagulant but also anti-inflammatory properties (reducing lung inflammation and improving oxygenation) and also has potential antiviral properties. The purpose of our study was to analyze the availability and range of anticoagulants used to treat coronavirus disease (COVID-19) and post-COVID syndrome in Ukraine. The materials of our study were the data of the State Register of Medicines, the Compendium directory, the Register of wholesale selling prices for medicines and the prices for anticoagulants in Lviv pharmacies. We have analyzed the domestic market of low molecular weight heparins used for the treatment of coronavirus disease (COVID-19) and post-covid syndrome according to the international non-proprietary name, taking into account all forms of production, manufacturers and prices. It has been established that in the pharmaceutical market of Ukraine these medicines are represented by 9 trade names, which in turn are divided according to the amount of active substance in 1 ml of solution. Analyzing the manufacturing companies, it was found that more than half (52.6%) of the presented heparins were produced in Ukraine, and 47.4% of the trade names of drugs are imported. The state of supply and prices for low molecular weight heparins in pharmacies in Lviv was analyzed. It has been established that the pharmacies of the city are provided with a sufficient amount of these medicines, manufacturers and dosages are widely represented. Although the current number of active patients coronavirus disease (COVID-19) in Ukraine has decreased compared to 2021, there is still a large number of patients who are treated with anticoagulants after an illness as a preventive measure or rehabilitation. There fore, the provision of pharmacies with a wide range of anticoagulant drugs in sufficient quantity and variety of dosage plays an important role in providing pharmaceutical assistance to the population in full.